Galectin-1 Facilitates Macrophage Reprogramming and Resolution of Inflammation Through IFN-β - Yaseen, Hiba; Butenko, Sergei; Polishuk-Zotkin, Irina; Schif-Zuck, Sagie; Pérez-Sáez, Juan Manuel; Rabinovich, Gabriel Adrian; Ariel, Amiram (Frontiers in Pharmacology, 2020)
During the resolution of acute inflammation, macrophages undergo reprogramming from pro-inflammatory, to anti-inflammatory/reparative, and eventually to pro-resolving macrophages. Galectin-1 (Gal-1) is a bona fide pro-resolving lectin while interferon β (IFN-β) was recently shown to facilitate macrophage reprogramming and resolution of inflammation. In this study, we found Gal-1null mice exhibit a hyperinflammatory phenotype during the resolution of zymosan A-induced peritonitis but not during the early inflammatory response. This phenotype was characterized by reduced macrophage numbers, increased secretion of pro-inflammatory cytokines, such as interleukin-12 (IL-12), and reduced secretion of anti-inflammatory cytokines, such as interleukin-10 (IL-10). In addition, we found a delayed expression of the pro-resolving enzyme 12/15-lipoxygenase in macrophages and heightened levels of the inflammatory protease proteinase-3 (PR3) in peritoneal fluids from Gal-1null mice. Moreover, we observed sex-dependent differences in the inflammatory profile of Gal-1null mice. Notably, we found that IFN-β levels were reduced in resolution-phase exudates from Gal-1null mice. Administration of IFN-β in vivo or ex vivo treatment were able to rescue, at least in part, the hyperinflammatory profile of Gal-1null mice. In particular, IFN-β recovered a subset of F4/80+GR-1+ macrophages, restored IL-12 and IL-10 secretion from macrophages to WT values and diminished abnormal peritoneal PR3 levels in Gal-1null mice. In conclusion, our results revealed a new Gal-1-IFN-β axis that facilitates the resolution of inflammation and might restrain uncontrolled inflammatory disorders.